Case report: Anterior midline decompression of a cervical epidural abscess: Technical note and case series of seven patients - Zian, Ahmed; Arts, Mark P.; van der Gaag, Niels A. (Frontiers in Surgery, 2022)
Background A spinal epidural abscess (SEA) of the cervical spine is a relatively rare disease and is generally characterized by progressive neurological deterioration due to compression of the spinal cord. Up to 40% of cervical SEAs are located ventrally of the spinal cord. Urgent surgical intervention is warranted to decompress the spinal cord and collect material for cultures to guide antibiotic treatment. However, the optimal timing of the intervention is unclear, and the associated risk of spinal instability in the presence of an extensive infection is a significant clinical dilemma. Methods In this paper, we present a novel surgical technique to treat a cervical SEA by anterior decompression through a linear transvertebral midline approach. This technique has the advantage of effectively draining the ventrally located SEA and obtaining material for bacteria culture while maintaining spinal stability without additional instrumentation. Results This case study presents seven patients with cervical SEAs who were successfully treated with surgical decompression by this transvertebral linear midline technique and antibiotic treatment. Conclusion Anterior decompression through a linear transvertebral midline approach for a ventrally located cervical SEA is a safe and pragmatic surgical procedure to achieve spinal cord decompression and collect bacteria culture without destabilizing the cervical spine.